The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0019-5049.130821
|View full text |Cite
|
Sign up to set email alerts
|

Validation of modified Mallampati test with addition of thyromental distance and sternomental distance to predict difficult endotracheal intubation in adults

Abstract: Background and Aims:Intubation is often a challenge for anaesthesiologists. Many parameters assist to predict difficult intubation. The present study was undertaken to assess the validity of different parameters in predicting difficult intubation for general anaesthesia (GA) in adults and effect of combining the parameters on the validity.Methods:The anaesthesiologist assessed oropharynx of 135 adult patients. Modified Mallampati test (MMT) was used and the thyromental distance (TMD) and sternomental distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Because difficult or failed endotracheal intubations are one of the leading causes of anesthesia-related morbidity and mortality in anesthetized patients, there is a need for accurate tests to predict difficult intubation [6, 7]. The ability to identify patients at risk of difficult tracheal intubation is important especially in patients with apparently normal airways.…”
Section: Introductionmentioning
confidence: 99%
“…Because difficult or failed endotracheal intubations are one of the leading causes of anesthesia-related morbidity and mortality in anesthetized patients, there is a need for accurate tests to predict difficult intubation [6, 7]. The ability to identify patients at risk of difficult tracheal intubation is important especially in patients with apparently normal airways.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of DI in Indian population is 3.3%–21% in various studies enrolling 60–600 patients. [ 6 7 8 9 10 11 ] In a study of 330 patients, the authors demonstrated that incidence of difficult laryngoscopy and intubation was 9.7% and 4.5%, respectively, in Indian patients with apparently normal airways. They also reported very high (48%) incidence of ‘minor’ difficulty in intubation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] The literature is sparse on the incidence of DI in Indian patients undergoing surgery. [ 6 7 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mainly they can be mentioned: Wilson (S 75% and E 88%), El-Ganzouri (S 65% and E 94%), Arne (S 94% and E 96%), Karkouti (S 86% and E 96%), and Naguib original (S 81% and E 72%) [8]. Recall that Mallampati plus thyromental distance and sternum distance is the combination of physical tests with greater discriminative power, with a sensitivity of 100% and specificity of 92.7% [11].…”
Section: Predictors Of Difficult Airwaymentioning
confidence: 99%